ASEAN’S AMBIGUOUS ROLE IN RESOLVING SOUTH CHINA SEA DISPUTES - York, Michael (UI Scholars Hub, 2015)
Maintaining regional peace and security is a major concern for the Association of South East Asian Nations(ASEAN) while preserving strong and strategic ties with China is also imperative for the protection of regional economic and security interests. In a territorial dispute that involves most ASEAN nations to a different extent, delicately crafting a diplomatic solution to protect good working relations among ASEAN nations and China will become increasingly difficulty. China has been accused of intimidating and using other coercive tactics against the Philippines and Vietnam in its bid to claim large areas of the South China Sea against the interests of ASEAN member states. Despite these tensions, ASEAN, nor its member nations have “condemned‟ these actions, or sort to sanction the Chinese at the risk of damaging lucrative economic relations to the detriment of security and stability in the region. A lack of solidarity within the ASEAN community has the capacity to undermine its function and response which has thus far been limited in addressing this issue. This paper will discuss aspects of Philippine, Vietnamese and Indonesian government policy towards China and characterize ASEAN‟s role in resolving and managing the conflict. The Philippines and Vietnam have increasingly troubled and deteriorating relations with the Chinese, in contrast with the Indonesians, who are working expeditiously to strengthen ties with the Chinese across a plethora of foreign policy and defense cooperation issues. The prospect of a unified ASEAN response to the South China Sea territorial dispute remains unlikely. Indonesia‟s proposed code of conduct may be the first step in addressing peace and security, however is not a long term solution and governments throughout the region must continue ongoing robust diplomatic efforts through ASEAN, bilaterally and multilaterally, with international assistance and cooperation, to resolve these territorial disputes.